European investment in Latin America : an overview. - FUENTES K., Juan Alberto (1992)
Analyses some of the traits of foreign investment in Latin America, in general and European investment in particular. Shows that during the latter half of the 1980s, the level of European direct investment depended on the extent of European banks' exposure in the region and reflected the availability of debt paper in the countries where European firms were located.